Factors contributing to TshiVenda home language grade 7 learners' poor performance problem at Khavhambe Primary School, Vhembe East District, in Limpopo Province, South Africa - Neshakadza, Aifheli Isaac (My University, 2024)
The purpose of the study is to investigate the factors that contribute to the problem of poor performance by grade 7 learners in the Tshivenḓa Home Language subject at Khavhambe Primary School with the aim to improve their performance. The approach that was adopted is a qualitative approach with interviews, document analysis and observation as the chosen data collection instruments. A focus group research design was chosen to complement the qualitative approach. In this study the researcher used a social critical theory as the research paradigm to support the overall undertaking of the study. Six participants, namely five learners and one educator, were randomly sampled and the two data analysis techniques that were used are coding and interpretation. Amongst the overall findings of the study, are the following main findings: most learners struggle to read and write, some learners undermine the Tshivenḓa Home Language subject and they do not study it, neither do they prepare themselves when going to write a test or examination. Learners do not write their given schoolwork, instead they copy from other learners and lastly, parents/guardians fail to support their children in their studies (the Tshivenḓa Home Language subject or any other subject for that matter) as they are not helping them with their homework or show any interest in their children’s education. The researcher recommends the following: The Tshivenḓa Home Language educators are advised to allocate time in their weekly periods to train their learners to read and write. Parents/guardians are urged to develop a habit of reading stories to their children so that children will be fascinated and also encouraged to read for themselves. Learners should be encouraged to value their Home Language so that they take it seriously and study it as they do other subjects. Educators must identify learners who do not write schoolwork and try to discover the reasons behind that so as to help them. Parents/guardians must be part of their children’s studies by helping them with schoolwork, encouraging them to work hard and trying to provide them with the necessary help for their studies.
Thesis (M.A. (Language Education)) -- University of Limpopo, 2024
Keywords: Home language; Progress record; Adequate achievement; Moderate achievement; Elementary achievement; Progression; Focus group; Venda language -- Study and teaching (Elementary); Academic achievement; Language teachers